Studi Kecepatan Aliran Air dengan Menggunakan Tabung Pitot - Iqbal, Muhammad Taufik; Faisal, Zulvyah (Politeknik Negeri Ujung Pandang, 2018)
The tools and methods used in the measurement of water flow velocity are now very diverse, such as by using Venturi Meter, Orifice, Current Meter, Pitot Tube, and so forth. To learn more about water flow velocity measurement method, in order to improve professionalism in the field of water resources can be done research at Hydraulics Laboratory by researching Water Flow Analysis by Using Pitot Tubes. The research process will be carried out using three varied channel basis samples: reviewing the velocity of the water flow at the bottom of the channel with slippery base, reviewing the flow rate of the water on the gravel base channel, and reviewing the flow rate of the water on the channel with the decking concrete base. The expected result of this research is knowing the distribution of velocity in a cross section such as drainage channel, irrigation channel and river, so construction of water structure can be adjusted position placement in the open channel section. In addition it can be used as a reference in planning an open channel. One of the benefits to construction cofferdam construction speed distribution is to determine the dewatering system to be carried out during construction.Keywords— Flow Speed, Speed Distribution. Channel Basic Variations